2020
DOI: 10.1016/j.spmi.2019.106356
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of vibration and Coulomb effects in transport of spin-polarized electrons in a single-molecule transistor

Abstract: Tunnel transport of interacting spin-polarized electrons through a single-level vibrating quantum dot in external magnetic field is studied. By using density matrix method, the current-voltage characteristics and the dependence of conductance on temperature of a single-electron transistor were calculated. We found that a lifting of Coulomb blockade in external magnetic field happens in stages. The Franck-Condon steps associated with inelastic electron tunneling in our case are doubled due to contribution of tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In [49], the previous paper of the author of this paper with coauthors, was demonstrated that the number of Franck-Condon steps in the current-voltage characteristics of spintronic molecular transistor is doubled due to the Zeeman splitting. Furthermore, strong Coulomb correlations lead to the appearance of a region without steps.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In [49], the previous paper of the author of this paper with coauthors, was demonstrated that the number of Franck-Condon steps in the current-voltage characteristics of spintronic molecular transistor is doubled due to the Zeeman splitting. Furthermore, strong Coulomb correlations lead to the appearance of a region without steps.…”
Section: Introductionmentioning
confidence: 89%
“…The Hamiltonian of the system after two unitary transformations: i) the rotation of axes and ii) Lang-Firsov transformation (the description of calculation process has been provided in detail in Ref. [49]) takes the form of a sum of four terms: H l , which remains the same, H d , which now reads…”
Section: Model and Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…At low temperatures, measurements with extremely high energy resolution have observed very fine gate-dependent physical effects, such as the Coulomb blockade, Kondo effect and electron-phonon coupling. [24][25][26] It can provide rich information on the molecule, including electronic transitions between energy levels, molecular vibrations and changes in spin states. Furthermore, some molecular-scale physical effects can be controlled by specially constructing single-molecule FETs, including quantum interference, spin, thermoelectric effects, superconductivity, and so on.…”
Section: Xin Zhumentioning
confidence: 99%